Progressiveness of LAZISMU Jombang: Utilization-Accountability of Sadaqah Maslahah Funds - Ramadhanti, Nadzifah Amilia; Choiri, Muttaqin (Az-Zarqa': Jurnal Hukum Bisnis Islam, 2023)
Abstract: Zakat, infaq, and sadaqah (ZIS) influence the people's economy because they have a strategic role in alleviating poverty. Several cases of misappropriation of zakat funds some time ago caused a lack of public trust in an amil zakat institution. So, the utilization and accountability of funds in an accountable and transparent manner, especially infaq and sadaqah, which are flexible, is essential. This writing aims to determine the utilization and accountability of funds in the maslahah alms program at the Muhammadiyah Amil Zakat Institution (LAZISMU) Jombang Regency according to Government Regulation 14 of 2014. This writing method uses field research, descriptive in nature, with a normative juridical approach. Data collection used is observation, interview, and documentation. Data analysis is inductive, which involves analyzing data based on the data obtained and then developing a specific relationship pattern. The result of this writing is that the application of PP 14 of 2014 in LAZISMU Jombang is in accordance with utilizing alms funds for maslahah needs which are in the form of necessities and utilization for employee loans used for employee maintenance or urgent employee needs whose purpose is for benefit. In addition, accountability has also been implemented with a report made every six months.Abstrak: Zakat, infak dan sedekah (ZIS) memiliki pengaruh terhadap perekonomian umat karena memiliki peranan yang sangat strategis dalam upaya mengentaskan kemiskinan. Adanya beberapa kasus penyelewengan dana zakat beberapa waktu lalu menyebabkan kurangnya kepercayaan masyarakat pada suatu lembaga amil zakat. Sehingga pemanfaatan dan pertanggungjawaban dana secara akuntabel dan transparan terutama infak dan sedekah yang sifatnya fleksibel sangat diperlukan. Artikel ini bertujuan untuk mengetahui pemanfaatan dan pertanggungjawaban dana pada program sedekah maslahah pada Lembaga Amil Zakat Muhammadiyah (LAZISMU) Kabupaten Jombang menurut Peraturan Pemerintah 14 Tahun 2014. Metode penulisan ini menggunakan penulisan lapangan atau field research, bersifat deskriptif, dengan pendekatan yuridis normatif. Pengumpulan data yang digunakan adalah observasi, wawancara dan dokumentasi. Analisis data yang bersifat induktif dengan menganalisis berdasarkan data yang diperoleh selanjutnya dikembangan dengan pola hubungan tertentu. Hasil penulisan ini yaitu penerapan PP 14 tahun 2014 di LAZISMU Jombang sudah sesuai dengan memanfaatkan dana sedekah untuk kebutuhan maslahah dimana berupa sembako dan pemanfaatan untuk pinjaman karyawan yang digunakan untuk maintanance karyawan atau kebutuhan mendesak karyawan yang tujuannya untuk kemaslahahan. Selain itu, mengenai pertanggunjawaban juga sudah diterapkan dengan adanya laporan yang dibuat selama enam bulan sekali.